Magical Realism in Leslye Walton's The Strange and Beautiful Sorrows of Ava Lavender (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
This article focuses on the description of magical realism in Leslye Walton's debut novel The Strange and Beautiful Sorrows of Ava Lavender. This study applies Wendy B. Faris' characteristic of magical realism in order to uncover the magical realism within the novel. The result of this study confirms that this novel portrays all of Faris' characteristics of magical realism. They are: the irreducible elements represented by Ava's wings, the phenomenal world seen through Ava's normal life, the unsettling doubt coming from the doubts on Ava's wings, the merging realms portrayed by the transformation and apparition, the disruptions of time and space through the existence of odd plant and seasons.